Functional chemically modified graphene film: microstructure and electrical transport behavior. (4th October 2017) - Ma, Junsheng; Hou, Xueyan; Yu, Mingpeng; Hua, Jingzheng; Ren, Xinyu; Qiu, Hong; Wang, Rongming
Abstract: Graphene oxide (GO) sheets were synthesized via a modified Hummers method. GO dispersion with a high concentration of 6 mg ml −1 was chosen to form GO hydrogel, followed by chemical reduction to derive a free–standing reduced GO (rGO) film. According to the x-ray diffraction (XRD) analysis, it has a [0 0 1] crystalline orientation in the film thickness direction. The rGO film has a densely stacked laminated structure and highly anisotropic characteristic of electrical conductivities. The light-weight rGO wire also demonstrates its excellent flexible and fire-retardant characteristics. Stress–strain measurements revealed the mechanical properties of the GO film can got further improved after chemical reduction. Electrical transport measurement indicates that rGO film exhibit semiconducting behavior with negative temperature coefficient characteristic. A temperature dependence of the conductivity from 20 to 297 K reveals that the carrier transport mechanism is thermally activated band conduction above 200 K and three-dimensional (3D) Mott's variable range hopping below 100 K. The parameters such as a density of the localized electron states and a localization length of the wave function have been determined from the plot of conductivity versus (versus) temperature.